2021
DOI: 10.1159/000513182
|View full text |Cite
|
Sign up to set email alerts
|

Residence, Clinical Features, and Genetic Risk Factors Associated with Symptoms of COVID-19 in a Cohort of Older People in Madrid

Abstract: <b><i>Background:</i></b> The older population has been especially affected by the severe acute respiratory syndrome coronavirus 2 pandemic (COVID-19). <b><i>Objective:</i></b> The aim of the study was to explore the incidence, severity, mortality rate, clinical features, and risk factors of symptoms of COVID-19 in home-dwelling older people, and its association with type of residence, cognitive deterioration, and neurodegenerative diseases. <b><i>Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 38 publications
7
22
0
Order By: Relevance
“…Given that our COVID-19 subjects were symptomatic patients the results obtained by Hubacek and colleagues might not be in real contradiction to our results, as they found a significant difference when compared the symptomatic group of their COVID-19 subjects to the general population. In a cohort of 913 older volunteers in Spain, aged 75–90 years, similar results were achieved as it has been found that the Apo E4 allele was associated with the presence of symptoms and clinical severity of COVID-19 infection ( Del Ser et al, 2021 ).…”
Section: Discussionsupporting
confidence: 75%
“…Given that our COVID-19 subjects were symptomatic patients the results obtained by Hubacek and colleagues might not be in real contradiction to our results, as they found a significant difference when compared the symptomatic group of their COVID-19 subjects to the general population. In a cohort of 913 older volunteers in Spain, aged 75–90 years, similar results were achieved as it has been found that the Apo E4 allele was associated with the presence of symptoms and clinical severity of COVID-19 infection ( Del Ser et al, 2021 ).…”
Section: Discussionsupporting
confidence: 75%
“…ApoE e4e4 homozygotes were more likely to be COVID-19 test positives compared to e3e3 homozygotes [98] . These data were confirmed in a Spanish cohort of old people [99] . ApoE4 is also associated with increased SARS-CoV-2 susceptibility in both neurons and astrocytes [95] .…”
Section: Genetic Polymorphisms Affecting the Immune Response Against Covid-19 ( Table 2 )supporting
confidence: 66%
“…Moreover, potent PLpro inhibitors such as XR8-23 and XR8-24 represent chemical probe tool compounds to study the details of PLpro-mediated disruption of host immune response and autophagy; and their contribution to COVID-19 infection and progression, including "long-COVID" and potential genetic bias. 53,54 MATERIALS AND METHODS…”
Section: Discussionmentioning
confidence: 99%